Dimensional Stability of Two Polyvinyl Siloxane Impression Materials in Different Time Intervals - Aalaei Sh; Rezaei Adli A; Mansoorali MR; Gholami F (Shiraz University of Medical Sciences, 2015)
Statement of the Problem: Dental prosthesis is usually made indirectly; there- fore dimensional stability of the impression material is very important. Every few years, new impression materials with different manufacturers' claims regarding their better properties are introduced to the dental markets which require more research to evaluate their true dimensional changes. Objectives: The aim of this study was to evaluate dimensional stability of additional silicone impression material (Panasil® and Affinis®) in different time intervals. Materials and Methods: In this experimental study, using two additional silicones (Panasil® and Affinis®), we made sixty impressions of standard die in similar conditions of 23 °C and 59% relative humidity by a special tray. The die included three horizontal and two vertical lines that were parallel. The vertical line crossed the horizontal ones at a point that served as reference for measurement. All impressions were poured with high strength dental stone. The dimensions were measured by stereo-microscope by two examiners in three interval storage times (1, 24 and 168 hours).The data were statistically analyzed using t-test and ANOVA. Results: All of the stone casts were larger than the standard die. Dimensional changes of Panasil and Affinis were 0.07%, 0.24%, 0.27% and 0.02%, 0.07%, 0.16% after 1, 24 and 168 hours, respectively. Dimensional change for two impression materials wasn't significant in the interval time, expect for Panasil after one week (p = 0.004). Conclusions: According to the limitations of this study, Affinis impressions were dimensionally more stable than Panasil ones, but it was not significant. Dimensional change of Panasil impression showed a statistically significant difference after one week. Dimensional changes of both impression materials were based on ADA standard limitation in all time intervals (< 0.5%); therefore, dimensional stability of this impression was accepted at least until one week.